Вплив похідних 6-заміщених 3R-2H- [1,2,4] тріазино [2,3-c]хіназолін-2-онів (сполук МТ-279 ТА МТ-282) на центральну та церебральну гемодинаміку інтактних тварин та за умов моделювання гострого порушення мозкового кровотоку - Маринич, Л. І.; Степанюк, Г. І.; Пашинська, О. С.; Коваленко, Сергій Іванович; Воскобойнік, Олексій Юрійович; Marynych, L. I.; Stepaniuk, H. I.; Pashyns’ka, O. S.; Kovalenko, S. I.; Voskoboynik, O. Y. (My University, 2013)
Велике медико-соціальне значення проблеми судинних захворювань головного мозку зумовлене їхньою широкою поширеністю, важкістю перебігу, а також високими показниками інвалідизації та смертності населення [6, 9]. Верхівкою «айсберга» вказаних захворювань є гострі порушення мозкового кровообігу (ГПМК). Серед різних видів ГПМК лідируюче місце посідає ішемічний інсульт, смертність від якого протягом першої доби сягає 25 %. It was found out in the experiments on intact anesthetized rats that 6-substituted derivatives of 3R-2H- [1,2,4]triazin [2,3-c] quinazolin-2-ons (compounds MT-279 and MT-282 (10 mg / kg intravenously) as well as Vinpocetine (5 mg / kg intravenously) increase the volume rate of cerebral blood flow, without affecting blood pressure. The therapeutic use of the compound MT-279 (three times a day) on cats that suffered from acute ischemic stroke, caused the growth of volume rate of cerebral blood flow, normalization of arterial and central venous pressure. This compound MT-279 prevailed the reference drug being close in the effect on blood oxygen saturation.
The effect of 6-substituted 3R-2H- [1,2,4] triazino [2,3-c] quinazolin-2-ons (compound MT-279 and MT-282) on the central and cerebral hemodynamics of intact animals and under the acute ischemic stroke modeling
Keywords: похідні 6-заміщених 3R-2H- [1,2,4]тріазино [2,3-c]хіназолін-2- онів; вінпоцетин; об’ємна швидкість мозкового кровотоку; 6-substituted derivatives of 3R-2H- [1,2,4] triazinо [2,3-c] quinazolin-2-ons; vinpocetine; the volume rate of cerebral blood flow